Non-linear seismic analysis and vulnerability evaluation of a masonry building by means of the SAP2000 V.10 code. - Pasticier, Laurent
The aim of the paper is to explore the possibilities offered by SAP2000 v.10, a software package with user-friendly interface widely used by practising engineers, for seismic analyses of masonry buildings. The reliability of the code was first investigated by carrying out static push over (SPO) analyses of two walls, already analysed by other researchers using advanced programs. The equivalent frame modelling was employed in all analyses carried out. The code was then used to investigate the seismic performance of an existing two storey building typical of the north east of Italy, with the walls being made of roughly squared stones. An SPO analysis was performed first on the most significant wall, followed by a number of time history analyses aimed to evaluate the dynamic push over curves. Finally, the seismic fragility curves were derived, considering the seismic input as a random variable.
Keywords: Equivalent frame; Fragility curves; Incremental dynamic analysis; Masonry building; Push over analysis; SAP2000.